Mechanical loading modulates phosphate related genes in rat bone - Ashwini Kumar Nepal; Hubertus W. van Essen; Christianne M. A. Reijnders; Paul Lips; Nathalie Bravenboer (PLoS ONE, 2023)
Mechanical loading determines bone mass and bone structure, which involves many biochemical signal molecules. Of these molecules, Mepe and Fgf23 are involved in bone mineralization and phosphate homeostasis. Thus, we aimed to explore whether mechanical loading of bone affects factors of phosphate homeostasis. We studied the effect of mechanical loading of bone on the expression of Fgf23, Mepe, Dmp1, Phex, Cyp27b1, and Vdr. Twelve-week old female rats received a 4-point bending load on the right tibia, whereas control rats were not loaded. RT-qPCR was performed on tibia mRNA at 4, 5, 6, 7 or 8 hours after mechanical loading for detection of Mepe, Dmp1, Fgf23, Phex, Cyp27b1, and Vdr. Immunohistochemistry was performed to visualise FGF23 protein in tibiae. Serum FGF23, phosphate and calcium levels were measured in all rats. Four-point bending resulted in a reduction of tibia Fgf23 gene expression by 64% (p = 0.002) and a reduction of serum FGF23 by 30% (p<0.001), six hours after loading. Eight hours after loading, Dmp1 and Mepe gene expression increased by 151% (p = 0.007) and 100% (p = 0.007). Mechanical loading did not change Phex, Cyp27b1, and Vdr gene expression at any time-point. We conclude that mechanical loading appears to provoke both a paracrine as well as an endocrine response in bone by modulating factors that regulate bone mineralization and phosphate homeostasis.